2018
DOI: 10.5603/imh.2018.0001
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of operations performed by the National Sea Rescue Institute of South Africa over a 5-year period

Abstract: Injury and illness, specifically drowning utilise a large proportion of search and rescue services. The results suggest further preventative measures and public health strategies be implemented to minimise traumatic and medical incident severity and subsequent casualties at sea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…The annual number of marine interventions by the BMPM was lower than in other specialized marine rescue structures [2,3]. The BMPM's rescue activity was not exclusive to the sea and its area of responsibility was geographically limited.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The annual number of marine interventions by the BMPM was lower than in other specialized marine rescue structures [2,3]. The BMPM's rescue activity was not exclusive to the sea and its area of responsibility was geographically limited.…”
Section: Discussionmentioning
confidence: 88%
“…The number of interventions requiring a physician increased in contrast to those that did not. There were an increased number of interventions in the summer with a peak frequency in August [2,4]. The peak in medical interventions between 4 p.m. and 6 p.m. was correlated with peak times in attendance.…”
Section: Discussionmentioning
confidence: 91%
“…Three (3) studies reported drowning in multiple sites (countries) [20,21,22]. Twenty-four (57%) of the articles originated from South Africa [20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43], three (7.1%) were from Ethiopia [20,44,45], Ghana [20,46,47], Malawi [20,48,49], Nigeria [50,51,52] and Uganda [53,54,55] respectively, while 2 (4.8%) studies were from Cote d’Ivoire [20,56], Kenya [20,57] and Egypt [21,22] respectively. One (2.4%) article each originated from Burkina Faso [20], Guinea [58], The Gambia [20], Tanzania [59], Seychelles [60] and Zimbabwe [61], See Figure 1 for location.…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly used data were surveillance data (46%) and death registers including hospital, police and coronial reports. Twelve (12) studies investigated and described drowning exclusively [21,22,23,24,25,26,27,30,43,50,54,60], while in 30 studies, drowning was reported as part of a wider study including studies investigation all cause of death and external causes of death [20,28,29,31,32,33,34,35,36,37,38,39,40,41,42,44,45,46,47,48,49,51,52,53,55,56,57,58,59,61]. Measures used to describe drowning were proportions and rates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation